THE IMPACT OF INFORMATION ASYMMETRY, MORAL HAZARD AND THE STRUCTURE OF FUNDING ON CORPORATE U.S. DOLLARS LOAN PRICING: THE EMPIRICAL STUDY IN INDONESIA THE PERIOD 1990-1997 - Deddy Marciano; Suad Husnan (Journal of Management and Business Review, 2014)
This study aims to answer the question: "What factors that influence the price of corporate loans in Indonesia?" And "Are there some differences in loan pricing between several types of creditors?". Furthermore, this research is to develop and test the loan pricing model that was developed in America and Europe to the context or setting in Asia, especially Indonesia. Different conditions and settings of the financial system between America/Europe and Asia, especially Indonesia, causing the loan pricing model that was developed in America/Europe can not be fully implemented for Indonesia. Key issues in this study consisted of: information asymmetry, moral hazard and funding structure. The first issue, information asymmetry consists of the type of creditors, foreign and domestic ownership, public and non-public ownership. The second issue, moral hazard problem consists of variables governmental and non-government ownership, and the special relationship between creditors and debtors. The last issue, creditors’ structure of funding is proxied by the ratio of CD / ML. In addition, this study also adobt the loan pricing models that are developed in America / Europe as control variables. This study also examines the argument of Strahan (1999) whether the loan fees also reflected the condition of the loan as well as loan spreads. The OLS regression (Ordinary Least Squares) with white correction method (White heteroskedasticity correction) for heteroscedasticity problem is conducted to test the model. Various samples and sub samples are prepared to answer various research questions and hypotheses. Testing between regression coefficients are conducted to examine differences in loan pricing between different types of creditors for each variable in the model. The test results generally show that only two new variables suggested by the study, namely: ownership and structure of funding have a significant contribution to the loan pricing model. For variable type of institution consisting of investment banks and commercial banks indicate that generally there is no difference in loan pricing between the two, only in some models of these variables are not significant with signs consistent.Ownership variable show results consistent with the hypothesis and significant effect on loan prices. While the variable special relationship between creditors and debtors have no effect on loan prices, it is due to inter-group loans made by conglomerates. For the case of capital costs of the creditor shows that the variable has a positive effect on lending rates set by creditors. Testing different regression coefficients lead to the conclusion that domestic creditors succeeded in detecting an increased risk of the debtor before the economic crisis of 1997 compared with foreign creditors.